Developing a Social Media Landing Page Specialist to Advance Creative Media MSMEs - Gumilang, Satria Akbar; Ramadhan, Bintang; Sahara, Siti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The increasing use of social media platforms such as Instagram and Facebook offers significant opportunities for businesses to reach a broader audience through organic content and paid advertisements. A landing page designed specifically for social media specialists is a crucial tool in digital marketing strategies. This type of landing page enables social media specialists to effectively showcase their expertise and services to potential clients. Utilizing a landing page template tailored to business needs can help attract and convert visitors into clients in a more professional and appealing manner. Instapage, as a platform offering such templates, provides various features, including modern design, strategic call-to-action (CTA) buttons, and A/B testing capabilities to optimize webpage effectiveness. The platform also facilitates the customization of designs to align with business branding, thereby enhancing the landing page’s role in not only showcasing expertise but also increasing the likelihood of converting visitors into loyal clients